Equation of state of alkane and alkylbenzene liquids: A test of the group contributions of scaling parameters for physical and chemical mixtures - (:unkn) unknown (KLUWER ACADEMIC/PLENUM PUBL, 2002)
The equation of state (EOS) data for physical and chemical mixtures have been studied in terms of the Simha-Somcynsky hole theory. In a previous paper, individual group attraction energy and repulsive volume quantities necessary for the description of interactions between the chemical constituents of alkanes and alkylbenzene were proposed, The previous method has now been extended to physical mixtures of alkanes and alkane-alkylbenzene through suitable decomposition equations for physical and chemical mixtures. A comparison of the theoretical EOS data, predicted by means of the proposed scaling parameters, and the experimental data is in reasonable agreement. The results confirm a basis for the EOS predictions and promote applications of the methodology to further systems.
Keywords: alkanes; alkylbenzene; equation of state; mixtures; Simha-Somcynsky theory; STATISTICAL THERMODYNAMICS; FLUIDS